38‐6: Transparent Display with High‐Contrast‐Ratio Reverse‐Mode PDLC. Issue 1 (28th June 2021) - Honda, Mariko; Murata, Koji; Nakamura, Kimiaki; Hasegawa, Tadashi; Haseba, Yasuhiro; Hanaoka, Kazutaka; Shimada, Shinji
Abstract : A chiral liquid crystal containing reverse mode PDLC (Ch‐R‐PDLC), which showed transparent state at 0V, was prepared. This Ch‐R‐PDLC achieved both low voltage driving and strong scattering simultaneously by optimizing the helical pitch length of the chiral liquid crystals and by using original mixtures of liquid crystals and monomers. Transmittance of the Ch‐R‐PDLC was 80% at 0V and 5% at 7V, which was comparable to the normal scattering type. This driving voltage was low enough to employ widely used drivers. A Ch‐R‐PDLC display that was bright in the ON state and highly transparent in the OFF state was also demonstrated.